Grapevine and Rose : Muslim Oral Ballads from Bosnia-Hervegovina - Belyavski-Frank, Masha (Book collections on Project MUSE., 2015)
"This anthology contains a range of ballads, including those with historical and cultural references, as well as references to traditional Bosnian folk beliefs. Included are well-known ballads, such as 'Hasanaginica', also known as 'What gleams white on the green mountain', as well as two ballads on the death of the Moric´ brothers of Sarajevo."--Page [4] of cover.